The impact of Covid-19 on records of american tegumentary leishmaniasis in Brazil: an ecological study - Dornels Freire de Souza, Carlos; Miranda Lago, Adriele; Farias de Barros Melo , Bernard; Sousa Carvalho, Victor Emanuel; Moreno de Oliveira Fernandes, Tânia Rita; Feliciano do Carmo, Rodrigo (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
Aims: American tegumentary leishmaniasis (ATL) is a chronic infectious disease that is endemic in Latin America. It is a public health problem in Brazil. The control of ATL has become even more challenging in the face of the Covid-19 pandemic. In light of this, this study aims to quantify the impact of the Covid-19 pandemic on American tegumentary leishmaniasis records in an area of northeastern Brazil. Methods: This is an ecological study that includes the notifications of all confirmed cases of ATL registered in the state of Pernambuco, reported in the Notifiable Diseases Information System (SINAN) from 2015 to 2022. The period 2015-2019 was used to calculate the expected value for the pandemic years (2020-2022). The expected values were compared with the observed values. Results: In the three years studied, 883 ATL diagnoses were expected in the state (294 records/year). However, 646 cases were reported, indicating an underreporting of at least 237 individuals (26.82% reduction). The impact observed in 2022 was the largest of the years evaluated: 111 individuals were no longer diagnosed (a 37.8% reduction). Conclusions: The Covid-19 pandemic had an impact on the control of ATL in Pernambuco. Actions are needed to reduce the underdiagnosis of the disease caused by the Covid-19 pandemic. KEY WORDS: ATL; epidemiology; leishmania; neglected tropical diseases; sars-cov-2